2017
DOI: 10.1155/2017/2050635
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Standard Precautions and Associated Factors among Healthcare Workers in Gondar University Comprehensive Specialized Hospital, Northwest Ethiopia

Abstract: Background. In many studies, compliance with standard precautions among healthcare workers was reported to be inadequate. Objective. The aim of this study was to assess compliance with standard precautions and associated factors among healthcare workers in northwest Ethiopia. Methods. An institution-based cross-sectional study was conducted from March 01 to April 30, 2014. Simple random sampling technique was used to select participants. Data were entered into Epi info 3.5.1 and were exported to SPSS version 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
119
10
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(149 citation statements)
references
References 23 publications
16
119
10
4
Order By: Relevance
“…4,5,6,8 Studies on the influencing factors of SP adherence have been investigated, including individual, work-related, and organizational factors 9 or sociodemographic, individual, and institutional factors. 10 Occasionally, factors such as knowledge, attitude, safety climate, protective device, and workload have been examined without distinction of categories. 11 Haile et al 10 reported that the sociodemographic factors reported to affect adherence to SP include being female, 11 length of work experience, 12 age, 13 higher level of education, 6,13 and department the nurse is stationed in.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,6,8 Studies on the influencing factors of SP adherence have been investigated, including individual, work-related, and organizational factors 9 or sociodemographic, individual, and institutional factors. 10 Occasionally, factors such as knowledge, attitude, safety climate, protective device, and workload have been examined without distinction of categories. 11 Haile et al 10 reported that the sociodemographic factors reported to affect adherence to SP include being female, 11 length of work experience, 12 age, 13 higher level of education, 6,13 and department the nurse is stationed in.…”
mentioning
confidence: 99%
“…10 Occasionally, factors such as knowledge, attitude, safety climate, protective device, and workload have been examined without distinction of categories. 11 Haile et al 10 reported that the sociodemographic factors reported to affect adherence to SP include being female, 11 length of work experience, 12 age, 13 higher level of education, 6,13 and department the nurse is stationed in. 6 Health belief, awareness, and risk perception have been identified as influencers of adherence to SP among individuals, 4,5,10,12 with results varying by country, hospital type, and subject.…”
mentioning
confidence: 99%
“…5,10,11 Other studies claim that nurses' inadequate knowledge about standard isolation precautions could explain why infection control activities are often carried out with poor results in health care settings. [12][13][14] However, other studies have claimed that education alone is not enough. 10,11 The Centers for Disease Control and Prevention encourage the implementation of training programs for health care workers about isolation precautions to prevent the spread of infectious diseases.…”
mentioning
confidence: 99%
“…The main recommendations of these studies were to focus on infection control in nursing curricula, provide more continuous education programs at the hospitals, apply more monitoring and supervision of standards and isolation precautions, and provide isolation structures and supplies in hospitals. 5,10,13,15,16 Few studies have investigated infection control knowledge and practice in Jordan. [17][18][19] Al-Rawajfah et al 17 reported nurses' lack of adherence regarding principles of infection control.…”
mentioning
confidence: 99%
“…This finding was congruent with the study conducted by Efstathiou et al (2011) who stated that, the most important factor to non-adherence of HCPs with protective barrier was the lack of protective equipment available. Haile et al (2017) added that, frequent unavailability of PPE could decrease the impulse of active staff and could be a reason for nonadherence. This finding goes in the same line with Hussain et al(2010), who reported that in relation to annual follow-up examination during the work for HCPs, it was found that the majority of the studied subjects were not done medical examination before working, while one fifth of the studied subject were done medical examination during work, thus there is increase the risk of spread of infection, absenteeism and disability.…”
Section: Part Iii: Resourcesmentioning
confidence: 99%